Potassium acetate-based treatment for thermally co-evaporated perovskite solar cells - Li, Jia (2021)
Thermal evaporation is a very successful and widely adopted coating technique for the deposition of organic and inorganic materials on rough and textured surfaces and over large areas. Indeed, this technique is extensively used in the semiconductor industry for the fabrication of organic light emitting diodes (OLEDs) and is commonly used in displays. In the last few years, thermal evaporated perovskite solar cells (PSCs) have also shown the potential to reach high power conversion efficiency (PCE) both on small and over large area devices. In this work, we present a detailed optimization of the potassium-based surface treatment used to improve the performances of our MAPbI PSCs fabricated using the thermal co-evaporation technique. Small area planar n-i-p PSCs with an active area of 0.16 cm achieved PCEs above 19% and the large area PSCs with an active area of 1 cm reached 18.1%. These un-encapsulated PSCs also proved an excellent long-term shelf stability maintaining 90% of their initial PCEs for over six months when stored at ambient temperature.